PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN PROSES DAN HASIL BELAJAR IPA SEKOLAH DASAR - Wiyoko, Tri; Putra, Randi Eka; Epriyani, Neta (Jurnal Tunas Pendidikan, 2022)
Science learning is declared successful if the predetermined learning objectives can be achieved. However, the results of the pre-observation show that there are problems in the process and learning outcomes of science in class IV SDN 17/II Tanah Grow. This research is a classroom action research (CAR) which was carried out in 2 cycles. Each cycle consists of planning, implementation, observation and reflection. The research instrument used to collect data consisted of observation sheets and learning outcomes test questions. The results showed an increase in the learning process carried out by educators from cycle I to cycle II with a good category, and the learning process of students increased from cycle I to cycle II with a good category. Furthermore, for the learning outcomes obtained by students after participating in learning with the discovery learning model, it showed an increase from the first cycle of 68% to 87.5% with a good category in the second cycle. So the discovery learning model can improve the process and learning outcomes of fourth grade students for science learning content.